For the following system, use the second equation to make a substitution for y in the first equation. 2x + y = 5 y + 3 = 2x
2x + 2x - 3 = 5
2x + 3 - 2x = 5
2x + 2x + 3 = 5

Respuesta :

Y=2x-3

The answer is 2x+2x-3=5

Answer:

option A: 2x+2x-3=5  

Step-by-step explanation:

[tex]2x + y = 5[/tex] is the first equation

[tex]y+3=2x[/tex] is the second equation

We need to use the second equation to solve for y

[tex]y+3=2x[/tex]

Subtract 3 from y to make y alone

[tex]y=2x-3[/tex]

Now we plug in 2x-3 for y in first equation

[tex]2x + y = 5[/tex]

[tex]2x + 2x-3 = 5[/tex]

option A is correct